A Systematic Review of Innate Immunomodulatory Effects of Household Air Pollution Secondary to the Burning of Biomass Fuels - Alison Lee; Patrick Kinney; Steve Chillrud; Darby Jack (Ubiquity Press, 2015)
Background: Household air pollution (HAP)-associated acute lower respiratory infections cause 455,000 deaths and a loss of 39.1 million disability-adjusted life years annually. The immunomodulatory mechanisms of HAP are poorly understood. Objectives: The aim of this study was to conduct a systematic review of all studies examining the mechanisms underlying the relationship between HAP secondary to solid fuel exposure and acute lower respiratory tract infection to evaluate current available evidence, identify gaps in knowledge, and propose future research priorities. Methods: We conducted and report on studies in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. In all, 133 articles were fully reviewed and main characteristics were detailed, namely study design and outcome, including in vivo versus in vitro and pollutants analyzed. Thirty-six studies were included in a nonexhaustive review of the innate immune system effects of ambient air pollution, traffic-related air pollution, or wood smoke exposure of developed country origin. Seventeen studies investigated the effects of HAP-associated solid fuel (biomass or coal smoke) exposure on airway inflammation and innate immune system function. Results: Particulate matter may modulate the innate immune system and increase susceptibility to infection through a) alveolar macrophage-driven inflammation, recruitment of neutrophils, and disruption of barrier defenses; b) alterations in alveolar macrophage phagocytosis and intracellular killing; and c) increased susceptibility to infection via upregulation of receptors involved in pathogen invasion. Conclusions: HAP secondary to the burning of biomass fuels alters innate immunity, predisposing children to acute lower respiratory tract infections. Data from biomass exposure in developing countries are scarce. Further study is needed to define the inflammatory response, alterations in phagocytic function, and upregulation of receptors important in bacterial and viral binding. These studies have important public health implications and may lead to the design of interventions to improve the health of billions of people daily.